2014
DOI: 10.1155/2014/912684
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Blood Pressure of Daily Lemon Ingestion and Walking

Abstract: Background. Recent studies suggest that the daily intake of lemon (Citrus limon) has a good effect on health, but this has not been confirmed in humans. In our previous studies, it was observed that people who are conscious of their health performed more lemon intake and exercise. An analysis that took this into account was required. Methodology. For 101 middle-aged women in an island area in Hiroshima, Japan, a record of lemon ingestion efforts and the number of steps walked was carried out for five months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…The results are consistent with our study. Although lemon was the most preferred one for HT, its effectiveness for decreasing blood pressure was not shown before certainly [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with our study. Although lemon was the most preferred one for HT, its effectiveness for decreasing blood pressure was not shown before certainly [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instances of lemon juice ingestion and the number of steps walked had been recorded for five months. The results indicated that daily lemon juice intake and walking were effective in reducing high blood pressure because both showed significant negative correlations with systolic blood pressure (Table 7) [63].…”
Section: Effects On the Cardiovascular Systemmentioning
confidence: 99%
“…[1,62] Effects on the cardiovascular system -Limiting myocardial damage (naringenin); -Decreasing blood fibrinogen; -Lowering blood pressure in people with hypertension. [1,11,63] Effects on the nervous system -Strengthening short-term memory.…”
Section: Mechanism Of Action Referencesmentioning
confidence: 99%
“…Citric acid showed hypotensive effects in normotensive mice, producing 23% and 71% reductions in mean arterial blood pressure at doses of 3 mg/kg and 15 mg/kg, respectively [ 65 ]; in our study, citric acid was administered at 104 mg/kg/day in HAR rats ( Table 1 ). In addition, an investigation on the consumption of lemon juice, walking, and blood pressures in 33–77 year-old Japanese women showed that blood citric acid concentrations negatively correlated with the changes in blood pressure [ 66 ]. Citric acid may promote the absorption of calcium and magnesium that could affect blood pressure [ 67 , 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%